Impact of recycled plastic content on bond line performance - Louisa, Eén; Wilma, Jönsson (My University, 2025)
Plastics are among the most widely used materials today, and increasing the use of recycled plastics is a key strategy for reducing CO2 emissions. This thesis investigates the impact of recycled polypropylene content and the bond line performance when joining components in the SPA3 battery for electric vehicles. The materials used in the study are virgin PP and the recycled plastics PIR30, PCR30, and PCR50. The abbreviation PIR stands for post-industrial recycled, and PCR stands for post-consumer recycled. The coupons are either untreated or treated with atmospheric plasma, plasma with precursor, or plasma followed by primer, respectively. After pretreatment, the plastic coupons were joined with a polyurethane-based two-component adhesive, and the strength of the joints was measured with single lap shear tests after curing and ageing. Surface analysis measurements of surface free energy, cleanliness, and surface roughness were also done to see the differences among the materials and how the surface properties changed after pretreatment. The result showed that the plasma pretreatment exclusively was superior among the pretreatments. Plasma-treated PIR30 and PCR30 received similar high strength as virgin PP, and plasma-treated PCR50 showed slightly lower strength. The results conclude that the recycled materials PIR30 and PCR30 are possible substitutes for virgin PP in the SPA3 battery package. PCR50 is also promising in this regard after optimisation and development when implementing high recycled polypropylene content.
Keywords: recycled polypropylene; polyurethane adhesive; surface-pretreatments; plasma; precursor; primer; SPA3 battery; electric vehicles